A homemade cost effective raman spectrometer with high performance - Montoya Rossi, Eduardo (2015)
The characteristics of a low cost, easy to construct, homemade Raman spectrometer are described and its performance presented and discussed. The light sensor of the spectrometer is a consumer grade EOS DSLR camera; the instrument uses a green laser pointer for signal excitation of transparent liquid samples, in transmission mode. The spectral resolution is approximately 15 cm-1.Construction, operation, calibration and image processing aspects are explained in detail. Good quality Raman spectra obtained for few pure liquids (benzene, carbon tetrachloride, and toluene) and mixtures (naphthalene – benzene – carbon tetrachloride and 96% volume rectified ethanol) are presented and discussed. It is proposed that the construction of the described spectrometer could be assigned as a project to student groups, under teacher guidance, providing a valuable opportunity of project based meaningful learning in several topics of Raman spectroscopy and optical instrumentation.